Investigation of different synthetic routes to and structure-property relationships of poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) - DRURY, ANNA; BLAU, WERNER (My University, 2003)
The synthesis of poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene) by Horner?Emmons and Wittig condensation polymerisation in three different solvents is described. The chemical and optical properties of the derivatives thus formed are analysed, especially in relation to the differences in the cis?trans ratio of the vinylene bonds. Although they all have the same chemical composition, it is found that their chemical and optical properties vary. NMR studies show that the morphologies of the polymers are different, due to the differences in the cis?trans ratio of the vinylene bonds. It is found that the derivatives produced by Horner condensation contain a majority of trans bonds, and these derivatives show different spectral characteristics to the Wittig derivatives. The ability of the polymers to disperse carbon nanotubes is also studied. Here, not only is the synthetic route important, but the solvent used also plays a role. The derivatives that are produced by the Horner condensation route in DMF or chlorobenzene are found to have the best binding capabilities with carbon nanotubes.
PUBLISHED
Keywords: poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene); poly(m-phenylenevinylene-co-2,5-dioctyloxy-p-phenylenevinylene)